Pembuatan Etanol Generasi Kedua Dengan Memanfaatkan Limbah Rumput Laut Eucheuma Cottonii Sebagai Bahan Baku - Wiratmaja, I Gede; Wijaya Kusuma, I Gusti Bagus; Suprapta Winaya, I Nyoman (Jurnal Energi Dan Manufaktur; Vol 5, No.1 April 2011, 2012)
Dissociation energy of diatomic crisis happened in various states in the existing world cleavage has entered areal serious step and concerns so that must soon is searched its the problem solving method, including Indonesia. Source ofpotential feedstock which its the availability is abundance, economy-priced, has not many exploited by people and containssimple sugar sewer structures which can be turned into ethanol is lignocellulosic material which in a few last decade,becomes one of interesting research object to know potency from material - lignocellulose material in producing ethanol.One of water territory commodity of a real Indonesia potency to be developed is sea grass Eucheuma cottonii and rest ofyield cottonii which is not is exploited able to exploited returns to to become one of making feedstock of substitution ethanolof feedstock which during the time is applied like distance, cassava and sugar cane. In this research, approach gone throughin the form of assaying method of direct is field. Assaying is done by comparing various raffle ratio cottonii with yeast atfermentation process with various fermentation time and various delignification to look for comparison of ethanol puritygrade, ethanol volume and fermentation speed by using measuring instrument which so called vinometer.Result fromresearch done with method is upper obtained result as follows : At delignification NaOH 15% and with comparison (1:0,006) for raffle cottonii and yeast is obtained by purity grade, best ethanol volume and fermentation speed. Where highestethanol grade got from treatment biologically that is equal to 15,5% and in physicist equal to 14,8% on day 6 offermentation. So do with ethanol volume yielded is higher where maximum volume capable to be yielded is 245 ml atbiological treatment and 234 ml at physical treatment on day 9of fermentation. Meanwhile highest fermentation speedcapable to be yielded is 0,058 kg/day at physical treatment, and 0,063 kg/day at biological treatment on day 3offermentation so that as a whole ethanol purity grade, ethanol volume and fermentation speed yielded with treatmentbiologically gives higher level result if it is compared to ethanol grade yielded from treatment in physicist.
Keywords: Delignification, vinometer,etanol